Effects of maternal dietary patterns and maternal obesity on children's obesity - Yılmaz, Feray Çağıran; Özçelik, Ayşe Özfer (MediHealth Academy Yayıncılık, 2022)
Aim: The effects of dietary patterns and dietary statuses of mothers on childhood obesity have not been understood clearly yet. This study aims to evaluate the dietary patterns of mothers and their dietary statuses on the obesity of children. Material and Method: This cross-sectional study included 295 mothers and their children, who were 2-6 years old. The participants' anthropometric measurements were carried out and the frequency of food consumption was also collected from the mothers in the study. Results: In the study, it was determined that the children of the participating mothers, who had high levels of income and education, had higher probabilities of being overweight/obese. Overweight/obesity in children was found to be significantly associated with maternal overweight/obesity (B=4.04, p
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi